Measurement of fatigue and wear of PEEK bush and A7075 cam plate in humanoid robot joints. (March 2014) - Koike, H.; Kanemasu, K.; Itakura, K.; Okazaki, S.; Takamiya, M.; Costa Santos, E.; Kida, K.
Abstract : Machine elements in humanoid robots for our life support require light weight, high accuracy and high output torque. In order to achieve low transmission error of the humanoid robot joints, wear of reinforced poly-ether-ether-ketone (PEEK) bushes against the 7075 aluminium alloy cam plates is investigated. Sliding fatigue wear tests of PEEK bushes in the humanoid robot leg joint were performed under various load torques. In the case of the bush under 127 Nm load torque at 5·7 mm s −1 sliding velosity, the backlash values were stable after the running process in fatigue wear test. PEEK film was formed by the friction between PEEK bush and 7075 cam plate under compression load. The oscillation angle of the output axis in the robot joint was stable after early stage because of the solid lublication caused by the film. This means the backlash value was stable and decreased due to the PEEK film between the bush and the cam plate.